PERILAKU PERJALANAN LANSIA DI KOTA YOGYAKARTA - , RAISA SAVITRI R; , dr. Lutfan Lazuardi, M.Kes., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Elderly people do not travel differently from those in other age groups, however special treatment still needed to handle the differences of their travel behavior. This is important because world demographics changing phenomenon, from productive population (young age group) into elderly population. Elderly population in Indonesia is projected to increase to 272.2% in 2040. Therefore, the Indonesian government is obliged to pay attention to the quality of life of elderly as mandated by law. The location of this research is Yogyakarta City, one of which have the highest life expectancy in Indonesia. This study uses a mixed method research (qualitative-quantitative) with qualitative-modeling analysis method. The research process through interviews guided by a questionnaire, on either weekly or monthly travel behavior of elderly. This is aim to identified the relationship between travel behavior and socio-demographic character of the elderly. The research found that the socio-demographic character does not affect the overall of the elderly travel behavior. However, the socio-demographic character only affect parts of the travel behavior such as modal choice alone or just travel distance. Also note that there are external factors that affect travel behavior such as help from elderly relatives, culture (ewuh pakewuh) and the participation of friends. Keywords: travel behavior, the elderly